CASPIAN DILEMMA: HOW TO DELIVER BLUE FUEL TO THE EUROPEAN MARKET - PREYGER, David; OMELCHENKO, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2005)
Globalization is increasingly encompassing regions traditionally closed to the outside world, including Central Asia. This is mainly having an effect on the relations between its countries and European states with respect to hydrocarbon deliveries and promoting the creation of a single geo-communication space. It is initially fraught with a certain amount of tension and discrepancy. But these negative elements will gradually abate, since the creation of this space is based on several objective integration factors. The most important of them include the formation of stability, security, and cooperation policies; mutually advantageous development of transnational communication lines; ensuring environmental balance; and protecting biological diversity. Recently, most Caspian countries, emboldened by the data of geological surveys on large supplies of hydrocarbons promising significant economic and political dividends, have been independently emerging from the shadow of the major political players onto the geopolitical battlefield. These dividends will make it possible for the Caspian countries to establish regulations in the region which will largely meet the interests of the regional elites and transnational companies. Of course, the priority issue in this struggle revolves around transnational communication routes, primarily deciding where to lay pipelines for delivering Caspian energy resources to the international markets. After all, pumping oil and gas not only ensures a stable source of hard currency paid for transit services, but also an efficient, as well as long-term, lever of political influence. In other words, the distribution of energy resources is becoming not only an economic, but also a sociopolitical problem of international cooperation and competition. So, all permissible (and others too) means and methods, from diplomatic and financial resources to specifically adjusted and precisely planned large-scale PR companies, are being launched into action. American, European, Turkish, Japanese, and Chinese companies, along with the states who own the subsurface, are taking active part in what is going on in the region. Their activity is related to the fact that in addition to the acute shortage of funds, modern technology, necessary equipment and materials, and qualified staff, the Caspian countries do not have direct access to solvent markets. What is more, most of these countries are dealing with extremely urgent social problems, and a certain amount of political dependence on the leading world nations plays an important role. All of this is prompting the leaders of the region’s republics to attract foreign capital into their countries’ economy, which of course dictates both the need for cooperation among investors and the inevitable rivalry among them.